PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KESEHATAN MENTAL SISWA MAN 2 JAKARTA - Sya'ban, Ziyah Fadilatus; Sutiono, Sutiono; Soraya, Syarifah (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
). Students' attitudes and behavior that are not in accordance with school norms are a reflection of the mental health of teenagers, so as an educator, a PAI teacher has the role of leading teenagers towards the gates of success to become a generation of high spiritual quality until they achieve a healthy mentality that can bring goodness to those around them. The aim of this research is to determine the role of Islamic religious education teachers in fostering the mental health of MAN 2 Jakarta students and what factors influence Islamic religious education teachers in fostering students' mental health. This research uses qualitative methods (field research) or field research by obtaining data that naturally describes the behavior of the object being studied. Data collection procedures through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The problem of this research was answered with the results of the role of Islamic religious education teachers in fostering the mental health of MAN 2 Jakarta students, namely; learning process (1) as an educator, providing a good example, (2) as a teacher creating an effective and enjoyable learning atmosphere, (3) as a mentor, helping students overcome learning difficulties, (4) as an advisor, providing advice to students who have problems with good way. As for fostering mental health using a preventive approach; instilling Islamic values ​​in students, getting used to worship, and educating of commendable morals. And through a repressive approach; punishment/punishment and appreciation. Among the factors that influence Islamic religious education teachers in fostering students' mental health are excessive use of gadgets, lack of parental role in supervising and controlling children, and the influence of friends.